Synthesis and evaluation of antifungal properties of a series of the novel 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and its analogues - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Kumari, Ratna; Bhat, Manoj Kumar; Deshpande, Mukund V.; Srinivasan, Kumar V. (Bioorganic & Medicinal Chemistry, 2007)
A series of 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and various analogues have been synthesized in excellent isolated yields starting from various arylidenemalononitrile and 3-amino-2-cyclohexen-1-one in 1-propanol as solvent at reflux temperature in the absence of any added catalyst. All the synthesized compounds were evaluated for their antifungal activity. The relationship between functional group variation and biological activity of the evaluated compounds is discussed in the article. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; antiproliferative activity; arylidenemalononitriles; arylquinoline carbonitrile; Michael addition

Cholesterol depletion by methyl-beta-cyclodextrin augments tamoxifen induced cell death by enhancing its uptake in melanoma - Mohammad, Naoshad; Malvi, Parmanand; Meena, Avtar Singh; Singh, Shivendra Vikram; Chaube, Balkrishna; Vannuruswamy, Garikapati; Kulkarni, Mahesh J.; Bhat, Manoj Kumar (Molecular Cancer, 2014)
Background: Despite modern advances in treatment, skin cancer is still one of the most common causes of death in the western countries. Chemotherapy plays an important role in melanoma management. Tamoxifen has been used either alone or in-combination with other chemotherapeutic agents to treat melanoma. However, response rate of tamoxifen as a single agent has been comparatively low. In the present study, we investigated whether treatment with methyl-beta-cyclodextrin (MCD), a cholesterol depleting agent, increases the efficacy of tamoxifen in melanoma cells. Methods: This was a two-part study that incorporated in vitro effects of tamoxifen and MCD combination by analyzing cell survival, apoptosis and cell cycle analysis and in vivo antitumor efficacy on tumor isografts in C57BL/6J mice. Results: MCD potentiated tamoxifen induced anticancer effects by causing cell cycle arrest and induction of apoptosis. Sensitization to tamoxifen was associated with down regulation of antiapoptotic protein Bcl-2, up-regulation of proapoptotic protein Bax, reduced caveolin-1 (Cav-1) and decreased pAkt/pERK levels. Co-administration of tamoxifen and MCD caused significant reduction in tumor volume and tumor weight in mice due to enhancement of drug uptake in the tumor. Supplementation with cholesterol abrogated combined effect of tamoxifen and MCD. Conclusion: Our results emphasize a potential synergistic effect of tamoxifen with MCD, and therefore, may provide a unique therapeutic window for improvement in melanoma treatment.
Keywords: Caveolin-1; Cholesterol; Methyl beta-cyclodextrin; Tamoxifen

Methylglyoxal attenuates insulin signaling and downregulates the enzymes involved in cholesterol biosynthesis - Deshmukh, Arati B.; Bai, Shakuntala; Aarthy, T.; Kazi, Rubina S.; Banarjee, Reema; Rathore, Rajeshwari; Vijayakumar, M. V.; H. V. Thulasiram; Bhat, Manoj Kumar; Kulkarni, Mahesh J. (Molecular Biosystems, 2017)
Methylglyoxal (MG) is a highly reactive dicarbonyl known to be elevated under the hyperglycemic conditions of diabetes and is implicated in the development of diabetic complications. Therefore, the current study investigates the role of MG in exacerbating insulin resistance at the insulin signaling level, as well as its effect on the global proteomic level. By using insulin sensitive rat muscle cells (L6) and Chinese hamster ovary (CHO) cells stably expressing the insulin receptor (IR) and a glucose transporter fused with green fluorescent protein (GLUT4-GFP), we have observed that MG impairs insulin signaling, inhibits GLUT4 translocation and reduces glucose uptake. SWATH MS analysis, a label-free quantitative mass spectrometric approach, showed altered expression of 99 proteins out of 2404 identified in response to MG treatment. These proteins are mainly involved in stress response, protein folding and proteolysis. Some of the deregulated proteins such as thioredoxin 2, glutathione S transferase, T complex protein 1 subunit beta (tcbp1), heat shock protein 90 and E3 ubiquitin ligase were previously reported to be associated with either diabetes or insulin resistance. Interestingly, aminoguanidine (AMG), a potent dicarbonyl scavenger, restored the deleterious effects of MG. For the first time, we report that MG induces downregulation of enzymes involved in cholesterol biosynthesis such as acetyl-CoA acetyltransferase, hydroxymethylglutaryl-CoA synthase, farnesyl pyrophosphate synthetase, squalene monooxygenase, and lanosterol synthase. GC MS analysis for sterol metabolites corroborated the proteomic results; MG significantly reduced cholesterol production whereas AMG treatment restored cholesterol production to levels similar to the control. Thus, MG leads to primary defects in insulin signaling and cellular abnormalities at the proteomic and metabolic levels, both of which may contribute to the development of insulin resistance.